Sistem Informasi Monitoring Peserta Magang Berbasis Web Pada Perusahaan XYZ - Stevania Setiawan; Hanifah Permatasari; Ridwan Dwi Irawan (LPPM Universitas Potensi Utama, 2024)
This research aims to address the issue of manually monitoring the attendance of interns at XYZ Company by developing a Web-Based Attendance Monitoring Information System. The system development method uses the Software Development Life Cycle (SDLC) approach. This system utilizes QR Code technology to facilitate the attendance process of interns, ensure data authenticity, and provide real-time monitoring. The research results show that this system can improve the accuracy of attendance data, reduce the potential for fraud, and simplify the management of interns for the company. The system also offers features for interns to view their attendance history, fill in logbooks, and request leave. Administrators can monitor intern attendance, view attendance reports, and manage intern data. The system is implemented using PHP Native and MySQL as the database. With this system, it is expected to increase efficiency and integrity in monitoring interns at XYZ Company.